Analysis of Isotopic Abundance Ratio of Consciousness Energy Healing Treated Metronidazole Using LC-MS and GC-MS Spectrometry - Branton, Alice; Kumar Trivedi, Mahendra; Trivedi, Dahryn; Jana, Snehasis (Journal of Advanced Pharmaceutical Science And Technology, 2020)
Metronidazole is an antibiotic and useful for the antibacterial and antiprotozoal medication. This study was performed to investigate the impact of the Trivedi Effect®-Biofield Energy Healing Treatment on the structural properties and the isotopic abundance ratio of metronidazole using LC-MS and GC-MS spectroscopy. Metronidazole sample was divided into two parts, one part of metronidazole was considered as control (no Biofield Energy Treatment was provided), while the second part was treated with the Trivedi Effect®-Consciousness Energy Healing Treatment remotely by a renowned Biofield Energy Healer, Alice Branton and termed as a treated sample. The LC-MS spectra of both the samples of metronidazole at the retention time (Rt) 2.61 minutes exhibited the mass of the protonated molecular ion peak at m/z 172 M+H+ (calculated for C6H10N3O3+, 172.07). The LC-MS based isotopic abundance ratio of PM+1/PM (2H/1H or 13C/12C or 15N/214N or 17O/16O) in the treated metronidazole was significantly increased by 8.24% compared with the control sample. Thus,13C, 2H, 15N,and17O contributions from (C6H10N3O3)+ to m/z 173 in the treated sample were significantly increased compared with the control sample. The GC-MS based isotopic abundance ratio of PM+1/PM in the treated metronidazole was significantly increased by 5.92% compared with the control sample. Hence,13C, 2H, 15N, and217O contributions from (C6H9N3O3)+ to m/z 172 in the Biofield Energy Treated sample were significantly increased compared with the control sample. However, the isotopic abundance ratio of PM+2/PM in the treated metronidazole was significantly decreased by 18.2% compared with the control sample. Hence,18O contributions from (C6H9N3O3)+ to m/z 173 in the treated sample were significantly decreased compared with the control sample. The isotopic abundance ratio of PM+1/PM (2H/1H or 13C/12C or 15N/14N or 17O/16O) and PM+2/PM (18O/16O) in the treated metronidazole was significantly altered compared to the control sample. From the results, it can be hypothesized that the changes in isotopic abundance and mass peak intensities could be due to changes in nuclei possibly through the interference of neutrino particles via the Trivedi Effect® - Consciousness Energy Healing Treatment. The new form of treated metronidazole would be better designing novel pharmaceutical formulations that might offer better therapeutic response against bacterial and protozoal infection in the vagina (bacterial vaginosis), stomach (giardiasis, trichomoniasis, pseudomembranous colitis), joints (pelvic inflammatory disease), liver, skin, brain, and respiratory tract, aspiration pneumonia, rosacea, intra-abdominal infections, lung abscess, fungating wounds, periodontitis, amoebiasis, oral infections, etc.
Keywords: Metronidazole; Isotopic Abundance Ratio; Liquid Chromatography-Mass Spectrometry (LC-MS); Gas Chromatography-Mass Spectrometry (GC-MS); Antibiotic